Making sense of fraction in elementary on montessori didactic materials - Rosalin, Rosalin; Tatang, Tatang (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to explore how Montessori didactic materials help elementary school students understand the concept of fractions. Using qualitative methods and a Design Didactic Research (DDR) approach, data were collected through classroom observations, semi-structured interviews with Montessori teachers, and documentation of student work. The data analysis technique used was thematic analysis, where the researcher identified patterns and main themes from the data collected. Triangulation was conducted to validate the research results by combining findings from interviews, observations, and documentation. The results showed that the use of concrete manipulative materials significantly improved students' understanding of fractions, developed problem-solving skills, and built a strong connection between abstract and real concepts. The teacher acts as a facilitator, allowing students to learn independently while still guiding them in the exploration process. This study concludes that the Montessori method is effective in teaching fractions at the primary school level, by providing a deep and meaningful learning experience for students.